Construction and evaluation of gold standards for patent classification—A case study on quantum computing. (June 2020) - Harris, Steve; Trippe, Anthony; Challis, David; Swycher, Nigel
Abstract: This article discusses options for evaluation of patent and/or patent family classification algorithms by means of "gold standards". It covers the creation criteria, and desirable attributes of evaluation mechanisms, then proposes an example gold standard, and discusses the results of applying the evaluation mechanism against the proposed gold standard and an existing commercial implementation.